Corporate governance effect on financial distress: evidence from Indonesian public listed companies - Rahmasari Ibrahim (Journal of Economics, Business, and Accountancy Ventura, 2018)
The study aims to determine the effect of corporate governance structures: managerial ownership, institutional ownership, independent commissioners, board of commissioners’ size, and board of directors’ size on financial distress. It used the sample taken from non-financial companies listed on the Indonesia Stock Exchange (IDX) for period 2012-2016. This study used a purposive sampling method involving 605 observations using binary logistic regression analysis techniques. The results show that there are significant negative impact between institutional ownership, size of board of commissioners and directors on financial distress. However, the results confirm that managerial ownership and independent commissioners had no significant impact on financial distress